Electronic structure of the antiferromagnetic phase of Sr2 Co2 O5 - Pardo, Víctor (2008)
Ab initio calculations analyze the properties of the G-type antiferromagnetic Sr2 Co2 O5 as a high-spin system. The description of the electronic structure is given; all the Co atoms are in a high-spin state with a small unquenched orbital angular momentum. Thermal analysis on a polycrystalline sample shows a magnetic phase transition at high temperatures.